The Response Dynamics of Various Bird Species to Recreational Activities and Nature Tourism in Gunung Gede Pangrango National Park - Avenzora, Ricky; Munajat, Mafut; Rachmatullah, Adam; Oktovianus; Oktavia, Reno Catelya Dira; Suprajanti, Dina Sri; Musoman, Ansyari (Jurnal Sylva Lestari, 2024)
Tourist activities in forest areas can potentially disturb wildlife, including bird species. One of the responses to such disturbances is avoidance. This study aimed to investigate and analyze the tolerance levels of various bird species to recreational disturbances in Gunung Gede Pangrango National Park, West Java, Indonesia. The method used in this research involved “dummy tourist activities” that varied by the distance tourists walked to the birds, the number of tourists, and the noise made by tourists. The results showed that forest birds had a maximum tolerance distance for tourist activities of around 10 m, while attractive birds had a maximum tolerance distance of around 20 m. The closest distance for tourists to observe all bird species was 5 m. It is concluded that all bird species had avoidance responses to various human or tourist disturbances. Raptors and colorful birds had low tolerance responses; songbirds had a medium tolerance, and forest birds had a high tolerance. Information on the response dynamics of various bird species to recreational activities is useful for creating tourism site planning and landscape design based on ecological wildlife carrying capacity. Keywords: avoidance response, birdwatching, disturbance response, ecotourism, Gunung Gede Pangrango National Park